Study of Actinotrichia fragilis Indonesian Red Seaweed as Raw Material for Healthy Salt - Nurjanah Nurjanah; Agoes Mardiono Jacoeb; Asadatun Abdullah; Joko Ahadi Priyanto; Naufal Muharam Nurdin; Anggrei Viona Seulalae (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2023)
Healthy seaweed salt is low sodium salt from seaweed that offers health benefits for hypertension patients. Indonesian seaweed has the potential to produce healthy seaweed salt. Research to date still focuses on green and brown seaweed but there is still no report for red seaweed. Actinotrichia fragilis is one of red seaweed species that has been discovered in Indonesia’s seawater and has not yet been utilized. Thus, this study aimed to determine the chemical composition and antioxidant activity of A. fragilis flour and the optimum ratio for producing seaweed salt with a high yield, optimum %NaCl, Na/K ratio, and antioxidant activity. Seaweed salt production treatment was the ratio of seaweed flour and distilled water 1:3, 1:5, and 1:10 (w/v), extracted at 40°C for 10 minutes. The mixture was filtered, then dried at 60°C for 30 hours. Data analysis was performed by analysis of variance. The raw material for dried A. fragilis seaweed has a high ash and low-lipid content. Then the ethanol extract had a total phenolic content value of 84.34 mg GAE/g and an antioxidant activity value of 98.22 mg/L. Furthermore, the antioxidant capacity of the ethanol extract was 60.15 mmol ascorbic acid/g and 552.21 mmol Fe2+/g. The best treatment for producing A. fragilis salt is 1:10 with yield of 12.76±0.13%, %NaCl 47.22±1.38%, Na/K ratio 3.32±0.18, IC50 with DPPH and ABTS method 113 mg/L and 87.27 mg/L, total antioxidant capacity 38.21 mg/mL ascorbic acid/g, and 304.32 mmol Fe2+/g. Furthermore, A. fragilis can be used for the production of  healthy seaweed salt.